FORMATION OF SINGING SKILLS IN STUDENTS THROUGH SARAHBORI DUGOH TARONA - Kodirov Davron Kobilovich (Bright Mind Publishing, 2025)
This scientific article describes the status of our national musical heritage, the attention paid to our school of performing arts, the special decisions made by our state, and the qualifications of students in sarokhbori Dugoh 2-3 singing. Methodical recommendations on singing sarakhbori Arcs 2-3 Tarot cards are given.
Keywords: Ajdodlar merosini o'rganish – avlodlar aqliga jon baxsh etuvchi bir obi-hayotdir, Decree of the President of the Republic of Uzbekistan dated November 17, 2017 No. pp-3391 ”on measures for the further development of Uzbek national Poppy art